IMMU-36. EVALUATION OF TUMOR DERIVED SERPINA3N IN EXPERIMENTAL GLIOBLASTOMA. (14th November 2022) - Wolf, Delaney; Ayasoufi, Katayoun; Zheng, Jiaying; Tritz, Zachariah; Jin, Fang; Hansen, Michael; Johnson, Aaron
Abstract: Glioblastoma (GBM) is an incurable brain cancer which is associated with severe peripheral immune suppression. Using experimental GBM, we recently determined that peripheral immunosuppression involves thymic atrophy, stunted T cell proliferation, and release of circulating factors that inhibit immune responses. RNA sequencing and proteomic studies have determined that transcripts and protein levels of Serpina3n are upregulated in the brain and serum of GBM patients and correlates with poor prognosis. We determined Serpina3n is a highly upregulated gene in the brain and the thymus of glioma-bearing mice using RNA sequencing technologies. Proteomic analysis of serum from glioma-bearing mice identified an upregulation of pathways associated with the extracellular expression of Serpina3n. We therefore sought to determine the role of Serpina3n in peripheral immunosuppression in GL261 glioma harboring wild type and Serpina3n knockout mice. Glioma implantation in Serpina3n knockout mice resulted in similar survival and peripheral immunosuppression compared to controls. Western blotting experiments confirmed that Serpina3n is expressed and secreted by GL261 gliomas isolated from WT and Serpina3n knockout mouse brains. Together this data suggests that tumor-derived, but not host derived, Serpina3n needs to be evaluated as a putative factor associated with peripheral immunosuppression.